Aplikasi Asam Giberelin(GA3) dan Naftalenacetate (NAA) untuk Menstimulasi Pertumbuhan Tanaman Philodendron xanadu - Safitri, Betari; Marveldani, Marveldani; Maulana, Erie (Universitas Lampung, 2023)
Philodendron xanadu is one of the leaf ornamental plants that much liked by society. Apart from being an ornament, P. xanadu also functions as an absorbent of toxic compounds contained inside the room. The potential development of P. xanadu is quite promising because the plant is widely used for decorating rooms and garden-forming elements. The growth rate of P. xanadu which derived from the separation of saplings is very slow, where the plant height is barely increased, but the addition number of saplings is very rapid / numerous. These conditions are unfavorable when used as an ornamental plant because the beauty of the plant is not optimally expressed. To overcome this, it is necessary to conduct research on the use of gibberellic acid (GA3) and naphthalmylene acetic acid (NAA) to spur the plant growth. The purpose of this study was to determine the influence of the use of GA3 and (NAA) to the growth of P. xanadu. The study was arranged factorial (2 factors) with a group randomized environment design. As the first factor is three levels of GA3 (0, 50, and 100 mg.l-1), and the second factor is 3 levels of NAA (0, 50, and 100 mg.l-1). Each experimental treatment was repeated 4 times. The results showed that the given of NAA and GA3 concentrations of 0, 50, and 100 mg.l-1 had no effect on the growth (leaf length) and the number of saplings P. xanadu. Keywords: GA3, NAA, Philodendron xanadu